The philosophy of modern song - Dylan, Bob, 1941- (Simon & Schuster, 2022)
In his first book of new writing since winning the Nobel Prize for Literature in 2016, Bob Dylan offers his extraordinary insight into the nature of popular music through a series of essays that double as meditations and reflections on the human condition.